Bats of Cat Tien national park: diversity, echolocation and taxonomic remarks - Thong, Vu Dinh (Academia Journal of Biology, 2015)
Cat Tien National Park is a hotspot in Vietnam for biodiversity research and conservation. The park, with its extensive areas of primary forest, wetland habitats and large mammal populations, is known worldwide for its outstanding landscapes and biodiversity. Prior to 2007, several bat surveys were carried out in the park. However, data on the park’s bats is still limited and the status of previous records of a number of species is unclear. Between 2008 and 2015, the author conducted a series of bat surveys in the park with emphases on taxonomy and echolocation. Bats were captured using mist nets and four-bank harp traps. Echolocation calls were recorded from inside a flight tent and in natural habitats. Results from the surveys and a literature review indicated that Cat Tien National Park is currently known to be home to 47 bat species belonging to 22 genera and 7 families. Of these, 19 species belonging to 10 genera and 5 families were recorded during field surveys between 2008 and 2015. This paper provides the most recent review of bat species from Cat Tien National Park. Remarks on taxonomy and echolocation frequencies of species complexes are also given in order to assist further research, training, education, management and conservation.